Improving Organizational Citizenship Behavior (OCB) Through Personality, Servant Leadership, Cultural Values, and Interpersonal Communication Using the POP-SDM Method - Eva Nurul Candra; Retnomawati, Rita; Lina Novita (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the influence of personality, servant leadership, cultural values, and interpersonal communication on the Organizational Citizenship Behavior (OCB) of private Madrasah Ibtidaiyah (MI) teachers in Tangerang City. The research used the POP-SDM method with a mixed method approach, which began with a qualitative study through interviews, FGDs, and preliminary surveys to identify the dominant variables, then continued with quantitative research using questionnaires on 150 respondents from 17 MIs in three sub-districts. Data analysis was performed using path analysis with the help of SPSS. The results showed that personality, servant leadership, and cultural values had a positive and significant effect on OCB. Servant leadership also had a significant effect on cultural values and interpersonal communication. Personality had a significant effect on interpersonal communication but did not have a significant effect on cultural values. Several indirect effects indicate that interpersonal communication acts as an intervening variable in the relationship between personality and OCB as well as between servant leadership and OCB. The differences in results from previous studies are influenced by the research context in the madrasah educational environment. This study confirms that teachers' OCB can be improved through personality strengthening, the application of servant leadership, the reinforcement of organizational cultural values, and the optimization of interpersonal communication as intervening variables.